PERSEPSI GURU DALAM MENGEMBANGKAN BAHASA ANAK MELALUI BERMAIN PERAN DI LUBUK ALAI - Ninda Islami Putri; Elise Muryanti (JCE (Journal of Childhood Education), 2021)
This research is motivated by the importance of teacher's role in process of children's language development through role playing method, because it can stimulate children's desire to learn and make children excited, so it is important to examine the teacher's views on children's language development through this method. This aims to find out how the development of children's language in role-playing method, to know the teacher's perception in developing children's language through role playing, and know the application of role playing in children's language development. The type of research used descriptive with a qualitative approach. The results obtained from this study are the development of children's language through role playing is carried out by giving instructions and introductions to children before and giving roles to children so that children are able to play and interact well; Teachers' perceptions of children's language development through role playing methods are very important because they are able to develop all aspects of children's development, especially children's language, such as increasing children's vocabulary and imagination, establishing social interactions through communication and language expression, helping children express their feelings and various other benefits; while in its implementation in the Sun Cluster Kindergarten it has been running according to expectations and obstacles that occur such as limited facilities can still be overcome. It can be concluded that the teacher's perception of the role playing method is role playing can develop all aspects of children's development, especially children's language, namely in increasing children's vocabulary.